Boden- und Klimaverhältnisse in Mittel- und Westeuropa während der Würmeiszeit - Poser, Hans (ERDKUNDE, 1948)
With the following remarks I present the results of two investigations, which represent an attempt to reconstruct the Worm Ice Age climate of the once non-glacial parts of Central and Western Europe with the help of climatic soil forms. Both investigations have already been published separately and in greater detail elsewhere (I), but here they receive only an actual summary, limited to the most essential and nevertheless supplemented and partly improved.